2020
DOI: 10.1021/acsami.0c14633
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Material Compatibility in CO2 Capture Systems Using Molten Alkali Metal Borates

Abstract: Molten alkali metal borates have been proposed as energy-efficient sorbents for the low-cost capture of CO2 at high temperatures. The molten sorbents could help to mitigate global warming by capturing CO2 from industrial sources and preventing the release of CO2 into the atmosphere. However, these novel materials operate under harsh conditions, introducing challenges of which material compatibility is one of the most important. Other than platinum, where a less than 0.1% change in performance was observed over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Valuable lessons may be learned also from hightemperature CO 2 -conducting membranes, where the molten carbonate needs to be retained within the porous solid matrix, 359,682−685 or salt-based energy storage systems. 686 Recently, Hatton et al 687,688 started to look into practical issues related to the use of molten salt-based sorbents for CO 2 (and potentially other gaseous species), in particular the compatibility with other materials in which the molten salt is contained (e.g., a vessel or pipes). They found that ceramics, stainless steel, and many superalloys (e.g., Inconel 600) are not suitable in combination with the molten salts investigated (Na 0.75 B 0.25 O 0.75 and (Li 0.5 Na 0.5 ) 0.75 B 0.25 O 0.75 ) owing to their corrosive oxidation and their contamination of the molten sorbent that decreases the sorbent's cyclic CO 2 uptake capacity.…”
Section: Future Development Of Sorbents On the Lab Scalementioning
confidence: 99%
“…Valuable lessons may be learned also from hightemperature CO 2 -conducting membranes, where the molten carbonate needs to be retained within the porous solid matrix, 359,682−685 or salt-based energy storage systems. 686 Recently, Hatton et al 687,688 started to look into practical issues related to the use of molten salt-based sorbents for CO 2 (and potentially other gaseous species), in particular the compatibility with other materials in which the molten salt is contained (e.g., a vessel or pipes). They found that ceramics, stainless steel, and many superalloys (e.g., Inconel 600) are not suitable in combination with the molten salts investigated (Na 0.75 B 0.25 O 0.75 and (Li 0.5 Na 0.5 ) 0.75 B 0.25 O 0.75 ) owing to their corrosive oxidation and their contamination of the molten sorbent that decreases the sorbent's cyclic CO 2 uptake capacity.…”
Section: Future Development Of Sorbents On the Lab Scalementioning
confidence: 99%
“…Our group has advanced molten alkali metal borates such as lithium borate (Li 3 BO 3 ) and mixed lithium, sodium borates as reversible CO 2 sorbents due to their large and temperature-reversible sequestration capacity for CO 2 and acid gases, which generally exceeds the capacity of other molten salts. 11–19 Thermoreversible reactions of the alkali metal borate glasses with CO 2 are well-documented. 11–20 The chemisorption of CO 2 by alkali metal (M) borate M 3 BO 3 results in the reversible formation of carbonate (M 2 CO 3 ), metal oxide (M 2 O)–boron oxide (B 2 O 3 ) binary compounds, and metaborate (MBO 2 ) as follows.4M 3 BO 3(l) + 3CO 2(g) ↔ 3M 2 CO 3(l) + M 6 B 4 O 9(l) 4M 3 BO 3(l) + 5CO 2(g) ↔ 5M 2 CO 3(l) + M 2 B 4 O 7(l) M 3 BO 3(l) + CO 2(g) ↔ M 2 CO 3(l) + MBO 2(l) 2M 3 BO 3(l) + 3CO 2(g) ↔ 3M 2 CO 3(l) + B 2 O 3(l) (M = Li, Na, K, etc .…”
Section: Introductionmentioning
confidence: 99%
“…11–19 Thermoreversible reactions of the alkali metal borate glasses with CO 2 are well-documented. 11–20 The chemisorption of CO 2 by alkali metal (M) borate M 3 BO 3 results in the reversible formation of carbonate (M 2 CO 3 ), metal oxide (M 2 O)–boron oxide (B 2 O 3 ) binary compounds, and metaborate (MBO 2 ) as follows.4M 3 BO 3(l) + 3CO 2(g) ↔ 3M 2 CO 3(l) + M 6 B 4 O 9(l) 4M 3 BO 3(l) + 5CO 2(g) ↔ 5M 2 CO 3(l) + M 2 B 4 O 7(l) M 3 BO 3(l) + CO 2(g) ↔ M 2 CO 3(l) + MBO 2(l) 2M 3 BO 3(l) + 3CO 2(g) ↔ 3M 2 CO 3(l) + B 2 O 3(l) (M = Li, Na, K, etc . ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of advantages of certain salts for CO 2 capture, including high capacities, fast kinetics, and excellent stability, have been demonstrated with molten alkali metal borates. ,, These materials may be tuned for entirely liquid phase reactions or for the phase change precipitation of reaction products, introducing opportunities to handle captured SO x and NO x impurities . As high temperature liquid phase materials, these sorbents are uniquely positioned, although a number of uncertainties and challenges remain around their corrosive nature and their practical operation at scale. , …”
Section: Sorbent Materialsmentioning
confidence: 99%
“…97,124,125 These materials may be tuned for entirely liquid phase reactions or for the phase change precipitation of reaction products, introducing opportunities to handle captured SO x and NO x impurities. 304 As high temperature liquid phase materials, these sorbents are uniquely positioned, although a number of uncertainties and challenges remain around their corrosive nature 305 and their practical operation at scale. 136,306 7.9.…”
Section: Sorbent Materialsmentioning
confidence: 99%